Synthesis of a copper-supported triplet nitrene complex pertinent to copper-catalyzed amination - Carsch, Kurtis M; DiMucci, Ida M; Iovan, Diana A; Li, Alex; Zheng, Shao-Liang; Titus, Charles J; Lee, Sang Jun; Irwin, Kent D; Nordlund, Dennis; Lancaster, Kyle M; Betley, Theodore A (Science (American Association for the Advancement of Science), 2019)
Terminal copper-nitrenoid complexes have inspired interest in their fundamental bonding structures as well as their putative intermediacy in catalytic nitrene-transfer reactions. Here, we report that aryl azides react with a copper(I) dinitrogen complex bearing a sterically encumbered dipyrrin ligand to produce terminal copper nitrene complexes with near-linear, short copper-nitrenoid bonds [1.745(2) to 1.759(2) angstroms]. X-ray absorption spectroscopy and quantum chemistry calculations reveal a predominantly triplet nitrene adduct bound to copper(I), as opposed to copper(II) or copper(III) assignments, indicating the absence of a copper-nitrogen multiple-bond character. Employing electron-deficient aryl azides renders the copper nitrene species competent for alkane amination and alkene aziridination, lending further credence to the intermediacy of this species in proposed nitrene-transfer mechanisms.